1990
DOI: 10.1093/arclin/5.4.325
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of gender effects upon verbal and visual memory performance in adults

Abstract: This study investigated gender effects on verbal and visual memory performance in normal adults (age range 18-91 years). The subjects were 140 volunteers (70 male, 70 female). Individuals in each male-female pair were matched within three years on age and two years on education. Shipley Vocabulary scores for the groups also were equivalent. Subjects were administered the Continuous Visual Memory Test (CVMT), Visual Reproduction subtest (VR), Verbal Selective Reminding Test (VSRT), and Expanded Paired Associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Considering the effects of our norms more closely, we found that age and sex had significant main effects on memory performance as expected, whereas education did not have a main effect. This is consistent with the well-established effects of age and sex on memory; namely memory declines as a function of age and females consistently outperform males across the age range (Kramer et al, 2003;Lundervold et al, 2014;Ragland, et al, 2000;Trahan & Quintana, 1990). However, we found no significant main effect of education level, most likely due to restricted variability in our sample.…”
Section: Discussionsupporting
confidence: 89%
“…Considering the effects of our norms more closely, we found that age and sex had significant main effects on memory performance as expected, whereas education did not have a main effect. This is consistent with the well-established effects of age and sex on memory; namely memory declines as a function of age and females consistently outperform males across the age range (Kramer et al, 2003;Lundervold et al, 2014;Ragland, et al, 2000;Trahan & Quintana, 1990). However, we found no significant main effect of education level, most likely due to restricted variability in our sample.…”
Section: Discussionsupporting
confidence: 89%
“…18 The VARK styles of learning showed significant differences along gender lines which is in line with previous studies. [19][20][21][22][23][24] The present study also examined the impact of learning styles on academic performance and mental health. Results of coefficients of correlations revealed that GPA was negatively and significantly related to the visual and kinesthetic type of learning.…”
Section: Discussionmentioning
confidence: 99%
“…We assessed crude models and models adjusted with education, relationship status, diet, and physical activity. All analyses were conducted separately in males and females, as alcohol consumption differs between the two sexes [ 61 ] and performance in visual memory tests, including the PAL test, has also been reported to be different in males and females [ 62 , 63 ]. Additionally, we performed multiple imputation by chained equations (MICE) on the drinking data, incorporating information on drinking habits and other covariates from both visits [ 64 ].…”
Section: Methodsmentioning
confidence: 99%